2011
DOI: 10.1074/jbc.m110.184010
|View full text |Cite
|
Sign up to set email alerts
|

Low Cholesterol Triggers Membrane Microdomain-dependent CD44 Shedding and Suppresses Tumor Cell Migration

Abstract: CD44 is a cell surface adhesion molecule for hyaluronan and is implicated in tumor invasion and metastasis. Proteolytic cleavage of CD44 plays a critical role in the migration of tumor cells and is regulated by factors present in the tumor microenvironment, such as hyaluronan oligosaccharides and epidermal growth factor. However, molecular mechanisms underlying the proteolytic cleavage on membranes remain poorly understood. In this study, we demonstrated that cholesterol depletion with methyl-␤-cyclodextrin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 52 publications
7
148
1
1
Order By: Relevance
“…Treating human glioma cells with the lipid-raft-disrupting agent methyl-β-cyclodextrin (MβCD), which extracts cellular membrane cholesterol, results in increased CD44 shedding mediated by a disintegrin and metalloproteinase 10 (ADAM10) (Murai et al, 2011). Moreover, the CD44 shedding induced by cholesterol lowering is not limited to glioma cells, but is also seen in other tumor cells such as pancreatic cancer cells (Murai et al, 2011).…”
Section: Lipid Rafts and Cancer Cell Migration And Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treating human glioma cells with the lipid-raft-disrupting agent methyl-β-cyclodextrin (MβCD), which extracts cellular membrane cholesterol, results in increased CD44 shedding mediated by a disintegrin and metalloproteinase 10 (ADAM10) (Murai et al, 2011). Moreover, the CD44 shedding induced by cholesterol lowering is not limited to glioma cells, but is also seen in other tumor cells such as pancreatic cancer cells (Murai et al, 2011).…”
Section: Lipid Rafts and Cancer Cell Migration And Invasionmentioning
confidence: 99%
“…It was recently demonstrated that lipid rafts play a crucial role in the localization and functionality of CD44 (Murai et al, 2011) (Figure 2B). Treating human glioma cells with the lipid-raft-disrupting agent methyl-β-cyclodextrin (MβCD), which extracts cellular membrane cholesterol, results in increased CD44 shedding mediated by a disintegrin and metalloproteinase 10 (ADAM10) (Murai et al, 2011).…”
Section: Lipid Rafts and Cancer Cell Migration And Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol modification and sigma-1 receptor agonist DHEAS could reduce ionomycin-induced ADAM10-dependent BTC shedding but not ADAM17-dependent HB-EGF shedding Cholesterol is a ligand for sigma-1 receptor (Palmer et al, 2007) and its depletion can affect lipid raft formation and both ADAM10-dependent shedding (Murai et al, 2011) and ADAM17-dependent shedding (von Tresckow et al, 2004;Zimina et al, 2005;Tellier et al, 2006Tellier et al, , 2008. Therefore, we tested the effect of cholesterol in our system.…”
Section: Resultsmentioning
confidence: 99%
“…Those two transmembrane proteases are also involved in the shedding process of many other substrates, such as ligands of the epidermal growth factor receptor (EGFR), Notch1, L1 cell adhesion molecule (L1CAM), which are involved in pathological processes and human diseases such as cancer and stroke (Pruessmeyer and Ludwig, 2009). It is now known that lipid rafts can affect both ADAM17 and ADAM10 function as cholesterol depletion can trigger both ADAM10-mediated CD44 shedding (Murai et al, 2011) and ADAM17-mediated CD30 shedding (von Tresckow et al, 2004), collagen XVII shedding (Zimina et al, 2005), and TNF shedding (Tellier et al, 2006(Tellier et al, , 2008. It has been reported that ADAM10 is located in the nonraft region of the membrane of neuroblastoma SH-SY5Y cells when functioning as α-secretase of APP (Harris et al, 2009) and it cannot cleave APP in a cholesterolrich environment (Kojro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%